Living with diabetes - case study - Markowska, Renata; Garczynski, Wojciech; Szczepanska, Anna; Zukow, Walery (Journal of Education, Health and Sport, 2011)
Introduction. Diabetes is a chronic disorder of metabolism. It is caused by impaired insulin secretion and action. There are type 1 diabetes, type 2 diabetes, gestational diabetes and other specific types of diabetes. Risk factors for this disease include age (risk increases after 45 years of age), obesity, low physical activity, hypertension, lipid disorders genetics. Symptoms of the disease are frequent urination, excessive thirst, weakness, lethargy, emaciation, fungal infections, furunculosis. Patients have elevated blood glucose levels. Complications of diabetes can be divided into acute and chronic. Complications include acute hyperglycemia and hypoglycemia. Chronic complications is microangiopathy (retinopathy, nephropathy, neuropathy) and macrovascular disease (myocardial infarction, stroke, peripheral vascular disease). Diabetes occurs more frequently, is an important sociological and social problem. Her diagnosis always causes anxiety, uncertainty, sense of danger. Ill try to find answers to many questions. Objective. The aim of this study was to determine the quality of life for patients with diabetes, diagnosis of care problems, patient education in terms of information essential for living with chronic disease. Materials. Material - the subject of research was a woman aged 64 suffering from diabetes type II. Patient presented information about diabetes, we got to know her health problems and their solutions. Methods. A Study of the individual case. Techniques: Observation, interview, examination of documents. Research problems posed in the work are: What are the health problems common in patients with diabetes? The extent to which a patient with diabetes is capable of self-care and self-control? As the nurse prepares the patient to change and lifestyle modification in chronic disease that is diabetes? The paper presents a range of activities including patient self-care and self-control. Results. The patient reported the following health problems relating to diabetes: the lack of insulin, inability to use the meter, the lack of sufficient knowledge about the complications of diabetes, skin abrasion on the foot and clammy skin between the toes, being overweight. Conclusion. Patient is a walking, self-contained. All nursery operations performed alone. With the support of her daughter is trying to overcome all the difficulties associated with the disease. She uses medical care as a medical indication, every 6-8 weeks in primary exercise control study of blood glucose levels, use of medical visits, always ordered the hypoglycemic drugs, insulin, diabetic diet, was informed by a nurse for further care and self-control. The paper presents a range of activities including patient self-care and self-control. The patient was informed of the need for lifestyle changes such as diet, avoidance of drugs, the constant control of blood glucose (glucometer training will be offered), a small regular exercise, etc. First of all making clear to patient that diabetes is not cited, you can live with this disease, do not fall apart. The proper operation of treatment with a conscious discipline of the patient, can maintain good performance in life and personal life satisfaction. She learned to use the same meter and examine the level of blood sugar at a specified time. She is aware of the problems associated with the disease. He is aware that only applies to the stringent requirements and restrictions, will allow it to avoid future complications. Despite an incurable disease is trying to discern the meaning of life and the meaning of their sacrifices. He believes in the fact that a positive attitude to the disease is part of the success on the road to quality of life.